The potential risk of tree regeneration failure in species-rich Taba Penanjung lowland rainforest, Bengkulu, Indonesia - AGUS SUSATYA (Biodiversitas Journal of Biological Diversity, 2018)
Susatya A. 2018. The potential risk of tree regeneration failure in species-rich Taba Penanjung lowland rainforest, Bengkulu, Indonesia. Biodiversitas 19: 1891-1901. Tropical lowland rain forest is recognized by its high species richness with very few trees per species. It is also known for having tendency to outcrossing of its species with different floral sexualities, which requires the synchronization between flowering of its trees and the presence of pollinators. Such ecological attributes raise possible constraints for the forest trees to regenerate. The objective of the study was to assess the potential risk of failed regeneration for each tree species of the forest. Each of species with dbh of more than 5 cm in a one-ha plot was collected, identified, and its ecological criteria, including rarity, floral sexuality, seed size, and flowering phenology were determined. The potential risk of the failure of regeneration was calculated by summing all scores from Analytical Hierarchical Process of the criteria. The results indicated that the forest consisted of 118 species belonging to 69 genera and 37 families. Rare species accounted to 52.10% of the total species. Of the 118 species, the potential medium risk category contributed to 38.14%, and more than 33% were grouped into very high and high risk or were more prone to failed regeneration in the future. All rare dioecious species were categorized into very high and high risks. Only 21 species (17.79%) are listed in 2017’s IUCN red list. Among unevaluated species, 22 and 13 species were respectively included in very high and high potential risk categories. The results revealed more detailed potential risk of failed regeneration of tree species, and can serve as basic information to develop proper conservation management.